Effect of Seed Priming on Germination and Seedling Parameters of Cucumber (Cucumis sativus L.) in Lamjung, Nepal. - Rekha Badu; Santoshi Malla; Sara Rawal; Sandesh Thapa (Turkish Journal of Agriculture: Food Science and Technology)
Poor seed germination obstructs the early and uniform seedling emergence at the sub-optimal conditions which can be a major setback to early spring cucumber growers. Different seed priming methods ought to be efficient solutions for the problem. To standardize the best priming method, an experiment was laid out in a Completely randomized design at the Horticulture lab of IAAS, Lamjung Campus. The treatment consisted of demineralized distilled water (hydropriming), hormonal priming (GA3 100ppm and GA3 200 ppm), halopriming (NaCl 0.5% and KNO3 0.5%), and non-primed seeds as control. The seeds were soaked in the respective treatment for 24 hours and then dried to initial moisture content under shade conditions. Observation recorded significantly highest germination percentage in GA3 100ppm (19.25%) and hydro priming (19.25%). The lowest mean germination time was found in GA3 100ppm (4.19days) which was significantly at par with GA3 200ppm (4.33days) and hydro priming (4.48days). The germination energy was found highest in GA3 100ppm (39.58) followed by GA3 200ppm (33.65) and dry weight was recorded highest in hydropriming (0.0252g) followed by GA3 100ppm (0.0250g) whereas the highest root length was observed in KNO3 priming (12.955cm) which is statistically at par with hydropriming (11.42cm), GA3 200 ppm (10.872cm) and NaCl priming (10.42cm). The plumule length was observed highest in KNO3 (13.00cm) followed by NaCl (11.25cm). All primed seeds showed increased seedling vigor compared to the unprimed seeds. The study showed that applied treatment notably increased the germination characteristics and seedling stand.